KAJIAN SEAKEEPING KAPAL FERRY RO-RO 750 GT BERBASIS PENGUJIAN HIDRODINAMIKA - Ahmad, Mujahid Syaiful (ROTOR, 2018)
The Ferry Ro-Ro is a ship that functions to crossing inter island and to transport vehicles, passengers and goods. Building a ship requires a very large investment value so that the design of the ship is a very important consideration by conduct the intens study to determine the performance of a ship, one of them is the performance of the ship motion, endurance, and reliability while sailing which can be seen by conducting a hydrodynamic test in the form of a seakeeping test on the Ferry Ro-Ro Ship Model. This study conduct the seakeeping testing due to Ferry Ro-Ro 750 GT Ship Model which aims to predict the pattern of ship behavior by using the seakeeping test methods at Manoeuvering and Ocean Basin at Laboratorium Hidrodinamika Indonesia at Balai Teknologi Hirdoinamika - BPPT with th parameter Wave Height Hs = 2.50 m, Wave Period Tp = 9.00 s by heading 180 deg and 135 deg, and model scale is 1 : 21.19. The seakeeping test procedure for the Ferry Ro-Ro 750 GT Ship Model is based on ITTC No 7.5-02-07-02 standards. Testing of the ship model is conducted by using the method of free running where ship moving at a speed of 12 knots (actual scale). Analysis of measurement results is displayed in the form of Response Amplitude Operator (RAO) and statical analysis. The hydrodynamic test results in the form of a seakeeping test of Ferry Ro-Ro 750 GT Ship Model shows the value of Root Mean Square (RMS) of each direction of the ship relative to the direction of arrival of the wave (heading) 180 deg with roll value = 0.825 deg and pitch value = 2.231 deg. And heading 135 deg with roll value = 2.410 deg and pitch value = 1.797 deg, where NORDFORSK 1987 criteria standard for RMS roll value is 6 deg, and RMS pitch value is 1.5 deg. Keywords: Seakeeping, Ferry Ro-Ro, Hydrodynamics